2009
DOI: 10.1159/000260907
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Brain Cavernomas in Children

Abstract: Background: Cavernous hemangiomas are benign vascular hamartomas caused by developmental malformations of the vascular bed. They can be found in 0.3–0.7% of the population, whereas one fourth of these lesions occur in children. Methods: In the present study, we report on 16 cases of cavernomas surgically treated in our institute. From each patient’s file, the age, sex, lesion location, symptoms and follow-up were analyzed. Results: The most commonly presenting symptom was epilepsy. Radiological signs of acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…Extracting patient data from previous reports (9 series with 189 patients) demonstrates consistent, exceedingly high complete resection rates for these lesions (99% overall) ( Table 3). 2,5,10,12,13,15,19,27 Improved intraoperative navigation, intraoperative ultrasound, and now intraoperative MRI are key components to achieving this statistic. Our 2 cases of incomplete resection represent exceptional cases-one with a lesion entirely embedded in motor cortex without a safe corridor of access ( Fig.…”
Section: 512mentioning
confidence: 99%
See 1 more Smart Citation
“…Extracting patient data from previous reports (9 series with 189 patients) demonstrates consistent, exceedingly high complete resection rates for these lesions (99% overall) ( Table 3). 2,5,10,12,13,15,19,27 Improved intraoperative navigation, intraoperative ultrasound, and now intraoperative MRI are key components to achieving this statistic. Our 2 cases of incomplete resection represent exceptional cases-one with a lesion entirely embedded in motor cortex without a safe corridor of access ( Fig.…”
Section: 512mentioning
confidence: 99%
“…2,5,12 Of particular note is the marked increased risk for complications (not unexpectedly) for lesions in eloquent cortex. Only 2 patients (1%) across all reviewed series had worsening seizures after treatment, while 94% of patients were seizure free at follow-up.…”
Section: 512mentioning
confidence: 99%
“…1,2 The incidence of pediatric CCM is estimated to be 0.37% to 0.53%, which represents 25% of all CCM. 3 Because children possess unique physiological features during development, the surgical management of pediatric CCM patients differs from that of adult patients with CCM.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperatively patients' improved clinically and seizures were controlled in most patients, thereby justifying surgery as the treatment of choice. 2 However, recent studies on the treatment of haemangioma of infancy revealed that propranolol may be an effective treatment modality. 3 Based on that information we administered propranolol to a patient with a giant cerebral cavernous malformation and the lesion demonstrated a significant volume shrinkage.…”
Section: Dear Professor Kayementioning
confidence: 99%